Improving automotive tire defect in the vulcanization process by leakage bladders issues - tossapol kiatcharonepol; Penpisut Sawangnimitkul; Rattanaporn Rattanaporn; Kittiwat Sirikasemsuk (My University, 2024)
The primary objective of this project is to minimize defects in industrial tires resulting from issues with leaking bladders during the curing process. The project aims to reduce the current monthly defective tire production of 1,378.70 kilograms to a target of 1,240.83 kilograms per month, which represents a 10% reduction in defects. Utilizing the QC story methodology, QC 7-tools, and Quality Control techniques, a thorough examination of data and root cause analysis identified five significant factors contributing to defective tires caused by bladder leakage. These factors include 1) a lack of expertise in bladder inspection, 2) excessive usage of bladders, 3) contaminations on the bladder surface, 4) inadequate bladder lubrication and 5) oxidation occurring inside the bladder. To address these issues, a new operational procedure and training program were introduced, alongside modifications to the curing machine to mitigate the oxidation process. Over a span of two months, these changes resulted in a reduction in defective tires to 735.345 kilograms per month, equivalent to a 46.66% decrease in the problem, and a cost savings of 10,000 USD per year.
Keywords: Risk and Safety Analysis; Vehicle Dynamics and Control Systems; Plant Surface Properties and Treatments